3D polarization texture of a symmetric 4-fold flux closure domain in strained ferroelectric PbTiO3 films. Issue 5 (12th July 2016) - Tang, Y.L.; Zhu, Y.L.; Hong, Z.J.; Eliseev, E.A.; Morozovska, A.N.; Wang, Y.J.; Liu, Y.; Xu, Y.B.; Wu, B.; Chen, L.Q.; Pennycook, S.J.; Ma, X.L.
Abstract: Abstract : Although the strong coupling of polarization to spontaneous strain in ferroelectrics would impart a flux-closure with severe disclination strains, recent studies have successfully stabilized such a domain via a nano-scaled multi-layer growth. Nonetheless, the detailed distributions of polarizations in three-dimensions (3D) and how the strains inside a flux closure affect the structures of domain walls are still less understood. Here we report a 3D polarization texture of a 4-fold flux closure domain identified in tensile strained ferroelectric PbTiO3 /SrTiO3 multilayer films. Ferroelectric displacement analysis based on aberration-corrected scanning transmission electron microscopic imaging reveals highly inhomogeneous strains with strain gradient above 10 7 /m. These giant disclination strains significantly broaden the 90° domain walls, while the flexoelectric coupling at 180° domain wall is less affected. The present observations are helpful for understanding the basics of topological dipole textures and indicate novel applications of ferroelectrics through engineering strains.